Pemangsaan Propagul Mangrove Rhizophora sp. Sebagai Bukti Teori Dominance-Predation (Predation of Mangrove Propagule, Rhizophora sp. as Evidence of Dominance-Predation Theory) - Rudhi Pribadi; Achmad Muhajir; Widianingsih Widianingsih; Retno Hartati (Marine Science Department Diponegoro University, 2014)
Pemangsaan sering mentebabkan kegagalan propagul mangrove untuk tumbuh menjadi individu baru. Pemangsaan terjadi saat propagul masih bergantung pada pohon induk atau pra-penyebaran maupun setelah terlepas dan jatuh dari pohon induk atau paska-penyebaran. Penelitian ini bertujuan untuk mengetahui tingkat pemangsaan propagul Rhizophora mucronata Lamk., R. stylosa Griff. dan R. apiculata Blume di Desa Pasar Banggi, Kabupaten Rembang, Jawa Tengah. Penelitian terdiri dari 3 tahap yaitu penelitian pendahuluan untuk mengetahui dominasi spesies, penelitian deskriptif pada pra-penyebaran tentang pemangsaan propagul pra-penyebaran dan penelitian eksperimental untuk mengetahui hubungan antara dominasi spesies dengan tingkat pemangsaan propagul paska-penyebaran. Tingkat pemangsaan propagul pra-penyebaran R. stylosa terbukti paling tinggi tingkat pemangsaannya yaitu 61,06% (kisaran 45,40-76,05%), disusul R. apiculata 58,18% (47,41-68,00%) dan terendah R. mucronata 11,88% (7,06-15,71%). Selama 18 hari pengamatan tingkat pemangsaan propagul R. stylosa paling rendah di stasiun yang didominasi R. stylosa (46,67%) dibandingkan di stasiun yang di dominasi R. apiculata (63,33%) maupun R. mucronata (83,33%). Pemangsaan propagul R. mucronata paling tinggi di stasiun yang didominasi R. mucronata (95%) dibandingkan di stasiun yang di dominasi R. apiculata (55%) maupun R. stylosa (45%). Pemangsaan propagul R. apiculata paling rendah di stasiun yang didominasi R. apiculata (50% ) dibandingkan di stasiun yang di dominasi R. stylosa (70%) maupun R. mucronata (73,33%). Hasil penelitian ini berhasil membuktikan teori dominance-predation pada spesies R. stylosa dan R. apiculata, namun tidak pada R. Mucronata. Kata kunci: pemangsaan, propagul, pra-penyebaran, paska-penyebaran, mangrove Propagule predation on mangrove in some extent reduced its viability to grow into seedling. The predation could happened before (pre-dispersal) or after (post-dispersal) the propagule drop from the tree.The reasearch was conducted in Pasar Banggi, Rembang District, Central Java. The aim was to investigate the predation rate of Rhizophora mucronata Lamk., R. stylosa Griff. and R. apiculata Blume propagules pre-dispersal and post-dispersal. Firstly, preface experiment for find domination spesies in the location, Second, with applied descriptive-based survey sampling and field experiment methods. Than all propagules of five replication trees were harvested and checked for its condition on pre-dispersal step. The third, with post-dispersal study there were twenty propagules from each spesies and tied them with used nylon string and placed on the forest floor for 2 until 18 days and checked its condition every 2 days after placement. This study is also set for tested the Smith’s theory on propagule predation related to tree domination. Rhizophora stylosa propagule was most predated before they fall (mean 61,06%, range 45,40-76,05%), followed by R. apiculata (mean 58,18%, range 47,41-68%) and the lowest isR. mucronata with mean 11,88% (range 7,06-15,71%). After 18 days of experiment in the field R. stylosa propagule in R. stylosa–dominated area was the lowest predated (mean 46,67%) compared to propagule in the area dominated by R. apiculata (63,33%) and also in R. mucronata area (83,33) Predated R. mucronata propagule is the highest in the R. mucronata dominated area (mean 95%) compared with R. apiculata dominated area (mean 55%) and also in R. stylosa dominated area (45%). Pradated of R. apiculata propagule is the lowest in the domination area of R. apiculata (50% ) compared with R. stylosa area domination with (mean 70%) also R. mucronata (73,33%). The result showed that the theory of dominance-predation can be proved only for R. stylosa and R. apiculata spesies, but not for R. mucronata spesies. Keywords : propagule, predation, pre-dispersal, post-dispersal, mangrove